Relationship between the Echocardiographic Epicardial Adipose Tissue Thickness and Serum Adiponectin in Patients with Angina - Yun, Kyeong Ho (Korean Society of Echocardiography, 2009)
BACKGROUND: It is still unknown whether increased cardiac adiposity is related to the risk factors of coronary artery disease (CAD). We measured epicaridal adopose tissue (EAT) and mediastinal adipose tissue (MAT) using echocardiography and examined their correlations with CAD and serum adiponectin. METHODS: One hundred fifty three patients who underwent elective coronary angiography for chest pain were measured cardiac adiposity by transthoracic echocardiography. The correlations of cardiac adipose tissue with the presence and severity of CAD and the serum adiponectin level were examined. RESULTS: EAT was thicker in patients with CAD (1.8±1.4 vs. 3.8±1.9 mm, p<0.001), but MAT was not different according to the presence of CAD (2.9±2.8 vs. 3.5±2.5 mm, p=0.121). EAT showed a significant positive correlation with age (r=0.225, p=0.005), homocystein (r=0.289, p=0.001), fasting glucose (r=0.167, p=0.042), and fibrinogen (r=0.218, p=0.009), and a significant negative correlation with serum adiponectin (r=-0.194, p=0.016). EAT thickness (OR 11.53, 95% CI; 3.61-36.84, p<0.001) and low serum adiponectin (OR 2.88, 95% CI; 1.02-8.15, p=0.046) were independent predictors of obstructive CAD. However, MAT thickness was not associated with CAD. CONCLUSION: EAT was associated with the severity and risk factors of CAD and correlated with serum adiponectin level. In contrast with EAT, MAT was not associated with CAD and adiponectin.